Kinetics of methane production and biodegradation of linear alkylbenzene sulfonate from laundry wastewater. Issue 14 (5th December 2016) - Motteran, Fabrício; Braga, Juliana K.; Silva, Edson L.; Varesche, Maria Bernadete A.
ABSTRACT: This study evaluates the kinetics of methane production and degradation of standard linear alkylbenzene sulfonate (LAS) (50 ± 3.5 mg/L) and LAS from laundry wastewater (85 ± 2.1 mg/L) in anaerobic batch reactors at 30°C with different sources of inoculum. The inocula were obtained by auto-fermentation (AFM) and UASB reactors from wastewater treatment of poultry slaughterhouse (SGH), swine production (SWT) and wastewater treatment thermophilic of sugarcane industry (THR). The study was divided into three phases: synthetic substrate (Phase I), standard LAS (Phase II) and LAS from laundry wastewater (Phase III). For SGH, the highest values for cumulative methane productions (1, 844.8 ± 149 µmol—Phase II), methane production rate (70.8 ± 88 µmol/h—Phase II and 4.01 ± 07 µmol/h—Phase III) were observed. The use of thermophilic biomass (THR) incubated at 30°C was not favorable for methane production and LAS biodegradation, but the highest kinetic coefficient degradation ( k 1 app ) was obtained for LAS (0.33 ± 0.3 h) compared with mesophilic biomass (SGH and SWT) (0.13 ± 0.02 h). Therefore, both LAS sources influenced the kinetics of methane production and organic matter degradation. For SGH, inoculum obtained the highest LAS degradation. In the SGH inoculum sequenced by MiSeq-Illumina was identified genera (VadinCA02, Candidatus Cloacamonas, VadinHB04, PD-UASB-13) related to degrade toxic compounds. Therefore, it recommended the reactor mesophilic inoculum UASB (SGH) for the LAS degradation.